If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -6) + -6(x + -3) = x + 3 + -2(x + -3) Reorder the terms: 3(-6 + x) + -6(x + -3) = x + 3 + -2(x + -3) (-6 * 3 + x * 3) + -6(x + -3) = x + 3 + -2(x + -3) (-18 + 3x) + -6(x + -3) = x + 3 + -2(x + -3) Reorder the terms: -18 + 3x + -6(-3 + x) = x + 3 + -2(x + -3) -18 + 3x + (-3 * -6 + x * -6) = x + 3 + -2(x + -3) -18 + 3x + (18 + -6x) = x + 3 + -2(x + -3) Reorder the terms: -18 + 18 + 3x + -6x = x + 3 + -2(x + -3) Combine like terms: -18 + 18 = 0 0 + 3x + -6x = x + 3 + -2(x + -3) 3x + -6x = x + 3 + -2(x + -3) Combine like terms: 3x + -6x = -3x -3x = x + 3 + -2(x + -3) Reorder the terms: -3x = x + 3 + -2(-3 + x) -3x = x + 3 + (-3 * -2 + x * -2) -3x = x + 3 + (6 + -2x) Reorder the terms: -3x = 3 + 6 + x + -2x Combine like terms: 3 + 6 = 9 -3x = 9 + x + -2x Combine like terms: x + -2x = -1x -3x = 9 + -1x Solving -3x = 9 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -3x + x = 9 + -1x + x Combine like terms: -3x + x = -2x -2x = 9 + -1x + x Combine like terms: -1x + x = 0 -2x = 9 + 0 -2x = 9 Divide each side by '-2'. x = -4.5 Simplifying x = -4.5
| 8=9x+6 | | 20+-1x= | | C(x)=x^2-40x+405 | | Y-2y-3y-6=0 | | .05c=.08+7.50 | | x+5=5x+25 | | y-(-5)=-6(x-1) | | 2x-71.50=4308.50 | | x+(x+5)+(2x+11)=180 | | 3/4y-6=0 | | x-20+x= | | 695=13(k+5)+32 | | logx=0.45 | | 7b=85 | | 10(g-836)=740 | | 5x-5(-6-2x)=0 | | 5-7x=2x+8 | | 2-2y-3y=0 | | 9x-(3x+3)=4x-49 | | -2=6-x | | 29=2+3g | | 8(4w+9)=-8 | | 4x^2-11x+15=0 | | 9r+8s-5(8r-5s)= | | 3x^2+12x-24=-26 | | 1/3x^2-1/12x-1/6=0 | | 803=792-b | | -6(q-81)=-30 | | 4.3(4+2x)-4.2=13 | | 2(8x+4)=22x | | -10(s+5)=-101 | | Ln(5/x)=-2 |